Total chlorophyll as indicator of ripening mangoes (MANGIFERA INDICA L. C.V. CARABAO) - Train, Corry Quemado
Total chlorophyii of carabao mangoes were monitored from days 2 to day 10 after harvest and everyday thereafter vis a vis the physico-chemical characteristics such as pH, %Titrable Acidity, and % Total Soluble Solids.